Evaluation of the knowledge about stem-cells by undergraduate students of courses of the health area from Universidade Estadual de Londrina – what students know and what their opinions are - Rabello de Oliveira, Renata; de Siqueira, José Eduardo; Matsuo, Tiemi (O Mundo da Saúde, 2008)
Stem-cells are considered in this beginning of century a historical landmark in the new curative medicine and opens horizons for the future of science. Even taking into account advances in science, the appropriate study of these cells creates ambiguity regarding values. If on the one hand there is the prospect of curing diseases classified until recently as “incurable”, on the other hand, one questions its effectiveness and the use of human embryos. The information runs in a sped up rhythm when propagated by the media, leaving the university as a secondary source in the search for this information. This study had the aim of identifying the level of knowledge and information of pupils of the courses of the health area of State University of Londrina concerning the considered subject. For doing this, 42 (forty two) pupils of the medical and nursing course physiotherapy and pharmacy were interviewed. One evidenced that the majority of pupils still have much difficulty to discuss the conceptual aspects of stem-cells. Most of them show to be against a law that defines the beginning of human life and to the production of embryos for research purposes. They believe that cultural and religious factors must be considered in discussions on frozen human embryos and had evaluated disciplines such as Bioethics as insufficient and innocuous during undergraduate years.